Umbilical Endometriosis and the Unsuspecting Plastic Surgeon - Gouda, Nura Y.; Miles, Marshall G. (Archives of Clinical and Medical Case Reports, 2024)
Our article describes the case of a 31 y.o. woman who presented with an unbiopsied, painful umbilical mass that had been enlarging over the previous two years. Surgical excision under local anesthesia was planned with subsequent pathology report revealing a diagnosis of umbilical endometriosis. Our paper discusses this specific case in addition to a brief literature review encompassing diagnosis, pathophysiology, medical and surgical management, and other common differential diagnoses.